Stability of Implants Placed in Augmented Posterior Mandible after Alveolar Osteotomy Using Resorbable Nonceramic Hydroxyapatite or Intraoral Autogenous Bone: 12‐Month Follow‐Up. (13th November 2012) - Dottore, Alexandre M.; Kawakami, Paulo Y.; Bechara, Karen; Rodrigues, Jose Augusto; Cassoni, Alessandra; Figueiredo, Luciene C.; Piattelli, Adriano; Shibli, Jamil Awad
Abstract Purpose This prospective, controlled split‐mouth study evaluated the stability of dental implants placed in the augmented mandibular areas with alveolar segmental "sandwich" osteotomies using nonceramic hydroxyapatite (ncHA) or autogenous bone. Material and Methods This study included 11 bilaterally partially edentulous mandibular patients in a split‐mouth design. Alveolar augmentation osteotomies were performed bilaterally with interpositional ncHA graft (test group) or interpositional intraoral autogenous bone graft (control group). After 6 months of healing, four implants (two implants in each side) were placed in each patient. Forty‐four implants were inserted and loaded after 6‐month healing period. At 1‐year follow‐up, radiographic, prosthetic, and resonance frequency analysis parameters were assessed. Success criteria included absence of pain, sensitivity, suppuration, and implant mobility; absence of continuous peri‐implant radiolucency; and distance between the implant shoulder and the first visible bone contact (DIB) < 2 mm. Results After a 1‐year loading period, the overall implant survival rate was 95.45%, with two implant losses (one of each group). Among the surviving implants (42 out of 44), two did not fulfill the success criteria; therefore, the implant success was 90.90%. DIB was 0.71 ± 0.70 and 0.84 ± 0.72 mm for ncHA and autogenous bone grafts, respectively (p > .05). Implant stability measurements were similar between the groups during the 12‐month follow‐up (p > .05). Conclusion Within the limits of this study, the implants placed either in sites augmented with ncHA or autogenous bone seem to represent a safe and successful procedure, at least, after 12‐month follow‐up.